Letter : Save the Basque children - Perkins, J.
037-0159-001 COMMUNICATIONS - WRITE ON SEPARATE SHEETS FOR EACH SUBJECT. AMALGAMATED UNION OF BUILDING TRADE WORKERS OF GREAT BRITAIN & IRELAND. Approved Society No.257. Telegrams: "Buildcres, Clapcom, London." Telephone: Macaulay 2442 (3 Lines) Southall Branch. Secretary's Address 10 Warwick Road Southall Our Ref Your Ref Date June 2nd 1937 "Save the Basque Children" Sir Walter Citrine General Secretary T.U.C. Dear Sir, In reply to your appeal, I am instructed by the members of the above Branch to inform you that we have been contributing to the fund for the Relief of Children of Spanish Workers (Through the Internation Committee) ever since last October, as a result of which we have depleted our Incidental Fund & have had to borrow from other sources to Balance the A/c. & further the Branch has levied themselves 6d per week for the same purpose & as the contributions come in they are forwarded to the same organisation. Wishing you every success in the cause of the Spanish Children I am yours fraternally J. Perkins Bch Sec 292/946/37/159